Decadal changes in zooplankton biomass, composition, and body mass in four shallow brackish lakes in Denmark subjected to varying degrees of eutrophication. Issue 2 (2nd April 2020) - He, Hu; Jeppesen, Erik; Bruhn, Dan; Yde, Morten; Hansen, Jacob Kjerulf; Spanggaard, Lasse; Madsen, Niels; Liu, Wei; Søndergaard, Martin; Lauridsen, Torben L.
ABSTRACT: During the past century, many brackish shallow lakes worldwide have become eutrophic. How the zooplankton have responded to this development is not well elucidated. Here, we analysed the decadal changes (from 1999–2000 to 2017–2018) in zooplankton biomass, body mass, and potential top-down control on phytoplankton during summer in 4 Danish shallow brackish lakes (Lund Fjord, Han Vejle, Selbjerg, and Glombak) subjected to varying degrees of eutrophication. Significant reductions of zooplankton biomass, body mass, the ratio of large-sized cladoceran to total cladoceran biomass, and the ratio of zooplankton to phytoplankton biomass were observed in low to moderately vegetated lakes (Selbjerg and Glombak). However, in the macrophyte-dominated lake (Han Vejle), zooplankton biomass, body mass, and the contribution of large-sized cladocerans ( Daphnia spp.) to total cladoceran biomass increased without a corresponding increase in the zooplankton to phytoplankton biomass ratio, which may be attributed to the refuge effect of submerged macrophytes. Using the pooled dataset, multivariate analysis indicated that total phosphorus concentrations and fish abundance were the main drivers of shifts in the zooplankton community and that zooplankton body mass was strongly negatively related to fish abundance. From a lake management perspective, our results suggest that eutrophication, through increased fish predation and reduced submerged vegetation abundance, has major effects on zooplankton communities in temperate coastal brackish shallow lakes, and a reduction in the zooplankton grazing pressure on phytoplankton is predicted if the eutrophication process continues.